2014
DOI: 10.1097/sap.0000000000000099
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Contralateral Prophylactic Mastectomy and the Impact on Breast Reconstruction

Abstract: The incidence of CPM is increasing and is associated with younger age, white race, family history, and the use of breast reconstruction. Implant-based reconstructions predominate in this cohort. The added morbidity of a contralateral procedure is significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 22 publications
1
40
1
3
Order By: Relevance
“…Only a few small, single‐institution studies have explicitly examined the potential association of preoperative breast MRI in CPM use. These studies have shown between a 70% and 82% increase from the approximately 3% CPM rate, with MRI use . We report a lower increase in CPM, but significantly increased among women who receive a MRI.…”
Section: Discussioncontrasting
confidence: 42%
“…Only a few small, single‐institution studies have explicitly examined the potential association of preoperative breast MRI in CPM use. These studies have shown between a 70% and 82% increase from the approximately 3% CPM rate, with MRI use . We report a lower increase in CPM, but significantly increased among women who receive a MRI.…”
Section: Discussioncontrasting
confidence: 42%
“…In a survey of over 200 CPM patients, Soran et al showed that in addition to concerns for development of contralateral breast cancer, the availability of reconstruction was cited as a reason for undergoing CPM 9 . The possible link between decisions to undergo CPM and decisions for breast reconstruction are alluded to in a retrospective study of 446 mastectomy patients including 174 CPM patients performed by Pinell-White et al, which showed that women who underwent CPM were more likely to pursue breast reconstruction 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The availability of reconstruction was cited as a factor in favor of deciding to undergo CPM in a recent survey of 200 patients 9 . A separate retrospective study also showed that women who undergo CPM are more likely to pursue breast reconstruction 10 . The role of varying reconstructive strategies on decisions made for CPM is yet to be evaluated.…”
Section: Introductionmentioning
confidence: 95%
“…28e31 The majority of our cohort (w80%) sought reconstructive surgery and the most complex autologous procedures were also the most popular. Breast reconstruction adds substantially to the morbidity 28 and complications commonly affect the prophylactic side in bilateral mastectomy. 31,32 Whilst in the main, patients selecting CPM are satisfied, a proportion of patients will experience regret, issues with body image, challenges forming sexual relationships and lack feelings of femininity.…”
Section: Discussionmentioning
confidence: 99%